Implementation Of Supportive Psychotherapy In The Elderly In Jekan Raya District, Palangka Raya City - Syam'ani, Syam'ani; Kasuma , Wijaya A. (Jurnal Karya Nyata Pengabdian, 2025)
The elderly population is a heterogeneous population: Not all individuals in the elderly population require the same form of social services. This is because the elderly population, although overall included in the fragile health/welfare population group, but to varying degrees. This difference is seen not only from the health aspect (some are "healthy", half healthy half sick, acutely ill, chronically ill to terminally ill), but also from the psychological and socio-economic aspects. Social welfare services for the elderly require a link between all areas of welfare, including: health, social, religion, sports, arts, cooperatives and others. Supportive psychotherapy for the elderly is important considering: The "healthy" elderly population: functionally still not dependent on others, daily living activities are still full, although there may be limitations in terms of socio-economics that require several services, such as housing, income increase and other services. The health services needed are mainly in terms of prevention and promotion, one of which is supportive psychotherapy. Examining the description above, special services are needed for the elderly in the fields of health, socio-economic, psychological, welfare and even spiritual needs, so that an increase in the degree of health and quality of life of the elderly is obtained to achieve a happy, prosperous and useful old age for family and community life in accordance with their existence in the midst of society. Based on this, the D III Nursing Study Program of the Palangka Raya Ministry of Health Polytechnic designs a regular and scheduled activity in the form of Community Service activities entitled Implementation of Psychotherapy in the Elderly in Jekan Raya District, Palangka Raya City.